Can sural nerve injuries be prevented in posterior leg approaches? Stage 1: Ultrasound evaluation of a new method based on surface anatomical landmarks and sural nerve pathway. Issue 1 (February 2023) - Ruiz, Pablo; Poggio, Daniel; Sala-Blanch, Xavier; Cuellar, Daniel; Baduell, Albert; Garcia-Elvira, Rubén; Testa, Enrique Adrián
Category: Other; Other Introduction/ Purpose: The risk of sural nerve intersection with posterior leg approaches, and its potential risk of injury in some surgeries can range from 60% to 100%. Several authors have described methods to predict the path of the sural nerve through metric units of non-proportional distances, however these distances are altered by patient's height, leg length and body mass index (BMI); none has proposed a reproducible method, proportional to each person based on anatomical references. The aim is to describe ultrasonographically the distance and crossing zone between a new method, proportional to each person, based on a surface reference line and the position of the sural nerve. Methods: Descriptive cross-sectional study, performed between January to April 2022 in patients requiring foot surgery who met inclusion criteria. We located and marked by ultrasound the course of the sural nerve in the posterior aspect of the leg. Landmarks were drawn and marked with a straight line from the posterior aspect of the medial femoral condyle to the tip of the fibula. This line was divided into two equal segments and the distal half was subdivided into 4 zones, this way, we studied areas based on simple anatomical proportions for each patient. The distance between the references and the ultrasound position of the nerve was measured in these 4 zones, creating intersection points and safety areas. Location and distances of the sural nerve from the proposed landmarks were assessed. A size of 96 lower limbs (48 patients) was determined with 95% confidence interval and 80% power to SN concordance between the two legs greater than 15% of that reported in the literature. Results: 100 lower limbs (50 left; 50 right) assessed in 50 patients were included. Forty-four percent female (44/100) and 56% male (56/100). The median age was 45 (range: 22 - 74) years. The median height was 164 (range: 150 - 180) cm with a median BMI of 23.3 (range: 17.7 - 39.7) kg/cm2. The shortest median distance of the nerve passage was 2.9 mm from Point 2. The sural nerve intersection was 59% in Zone B, 19% in Zone C and 20% in Zone A. Safety zones were established. Average 80% of coincidence in sural nerve localization, in the distal half of the leg, in relation to the surface reference line when comparing both legs of each patient. Conclusion: This study proposes a simple, reproducible, non-invasive, and for the first time, person-proportional method that describes the distance and location of the main areas of intersection of the sural nerve with points and areas determined by a line guided by superficial anatomical landmarks.